Journal of applied bioanalysis - Hernández Meneses, Brenda Noemi; Jaramillo Cardona, Martha Cecilia; Sorzano-Rodríguez, Deisy Milena (My University, 2025)
Abstract: This article begins by examining the health dimension of forced migration, emphasizing challenges such as malnutrition, chronic stress, limited healthcare access, and heightened exposure to infectious diseases. To this end, a review of key theoretical approaches to human mobility was conducted, along with an analysis of emigration data and a general characterization of the border region. Applied analysis methods, including demographic health data and qualitative interviews, were used to capture both social and clinical aspects of the displacement experience. Subsequently, a qualitative analysis of border-crossing experiences was carried out, identifying emotional, physical, and economic impacts. This study highlights how forced migration generates not only social disruption but also measurable health risks, underscoring the need for integrated bioanalytical, clinical, and public health interventions. The findings carry important implications for health professionals, planners, and bioanalytical scientists seeking to design evidence-based responses to displacement.
JOURNAL OF APPLIED BIOANALYSIS
Keywords: Forced migration; Public ealth; Bioanalytical perspectives; Healthcare access; Development planning; Border Mexico-United States; Forced displacement; Campus Tijuana